(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Selective alkylation and cyanoethylation of 2H(methyl) benzimidazoles (1, 2), benzimidazolin-2-one (3) and -2-thione (4), benzothiazolin-2-thione (5) and 2-methyl-benzopyrimidin-4-one (6, 2-methylquinazolin-4-one) have been studied. It was found that in the case of alkylation of 2H(methyl)benzimidazoles and benzimidazolin-2-thione by aliphatic halogen carboxylic acid esters and / or amides reaction leads to the formation of selectively N3- and S-alkyl derivatives. Interaction of benzothiazolin-2-thione and 2-methyl-benzopyrimidin-4-one with acrylonitrile takes place mono-cyanoethylation, but in the case of benzimidazolin-2-one takes place di-cyanoethylation reaction. It was revealed that formation of mono- and / or di-substituted products 7-13 dependence on the structure of starting compounds and the reaction conditions (reaction temperature and time, ratio of reagents). It should be noted that the obtained compounds are important synthons for further investigations. The structure of synthesized compounds (7-13) was confirmed by IR- and 1H NMR-spectroscopy.